Pengembangan Kurikulum Pendidikan Agama Islam di Era 4.0 - Muhammad Zia Ul haq; Tasman Hamami (ISLAMIKA, 2020)
Islamic religious education faces the challenge of distortion in the era of industrial revolution 4.0. The development of digital technology makes it possible for everyone to access all kinds of information and connect quickly through the internet and it’s innovation (internet of things). The effects of a positive and negative potential technology for humans. Islamic religious education must be able to prepare human resources who believe and have morality and become Muslim intellectuals. The development of Islamic education curriculum is an effort in facing challenges in the era of the industrial revolution 4.0. This research uses the library research method by collecting and analyzing library data. The results of the research show that there is a need for adjustments in the curriculum of Islamic education in the 4.0 era. The goal of Islamic education is to make educated Muslim intellectuals. The learning method with a combination of conventional and technology is bleanded leraning. The content of the material must be adapted to the circumstances and skill requirements of the 4.0 era. Evaluation is comprehensive and is a shared responsibility (educational ecosystem). Educators must adjust and have the competencies needed in the 4.0 era. And infrastructure facilities adapted to technological development